Identity Crisis: The Construction and Role of Virtual Selfhood in Suicides - Dr. Farah Ashraf (South Eastern European Journal of Public Health, 2025)
The Internet and World Wide Web have woven together humanity in new ways, creating global communities, new forms of identity and pathology, and new modes of intervention. The Internet sites are transforming the ways emerging adults engage with others in their social worlds. This qualitative study examines communication processes of identity construction within social interactions among emerging adults using multiple social networking sites. The most common use of the Internet among youth is to communicate with peers (Subrahmanyam et al., 2001). Social networking sites are transforming the ways they do so as they become more widely used and replace face-to-face interactions with online exchanges (Boyd & Ellison, 2007). Because adolescents and emerging adults construct their identities through peer interactions (Erikson, 1959; Arnett, 2000), suicide is the second leading cause of death in youth aged 10–24 years old globally (Patton et al., 2009), examining the nature of their online communication is critical to understanding the potential implications of these technologies for the process of identity development. The goal of this study is to scrutinize how emerging adults present themselves to each other on social networking sites, as they construct a shared and relatively public social space in which images of the self are broadcast. This study also surveys (a) how the Internet is transforming human functioning, personhood, and identity through the engagement with electronic media; (b) how electronic networking gives rise to the emergence of new pathologies of the Internet, for example Internet addiction, group suicide, and cyber bullying, and imbalanced mental health concerns.